The Role of the Use of Social Media and Family Environment on Entrepreneurial Interest of Private University Students - PURWANTO, AGUS (Journal of Industrial Engineering & Management Research, 2021)
The purpose of this research are to analyze the correlation of the use of social media on student entrepreneurship interest and The family environment on student entrepreneurship interest. This type of research is research. The questionnaire was adapted from research that has tested its validity and reliability and several items were developed by researcher. The sampling technique used is simple random sampling, namely taking samples from members of the population that is carried out randomly because all members are considered homogeneous. Obtained 180 private university students who is taking a thesis as a respondent. Data analysis using Structural Equation Modeling (SEM) analysis with SMARTPLS software tools. Based on the results of data analysis, it is concluded that the use of social media has a significant effect on Student Entrepreneurial Interest, an increase in the variable Use of social media will have a significant effect on increasing the Student Entrepreneurial Interest variable and a decrease in the variable Use of social media will have a significant influence on the decrease in the Student Entrepreneurial Interest variable. The work environment has a significant effect on Student Entrepreneurial Interest, an increase in the work environment variable will have a significant effect on increasing the Student Entrepreneurial Interest variable